Topiramate as Monotherapy or Adjunctive Treatment for Posttraumatic Stress Disorder: A Meta‐Analysis. Issue 1 (1st February 2018) - Varma, Archana; Moore, Michael B.; Miller, Christopher W. T.; Himelhoch, Seth
Abstract: Posttraumatic stress disorder (PTSD) is a chronic and debilitating condition for which clinicians sometimes turn to anticonvulsants as a treatment for symptoms. This study was a systematic review and meta‐analysis of randomized controlled trials (RCT) that have assessed the efficacy of topiramate as monotherapy or adjunctive therapy, compared to placebo, for the treatment of PTSD in adults. Prescribers may be reluctant to turn to topiramate, given the commonly reported side effects of impaired cognition, sedation, fatigue, and headache. We searched PubMed, PsycInfo, and Cochrane Central databases for relevant trials. Five studies were identified as RCTs and thus met inclusion criteria; one additional nonpublished study was identified via phone contact with its authors. Of these six studies, one was excluded from the statistical meta‐analysis due to its high dropout rate (16 of 40 participants). One of these studies was excluded from a stratified analysis of symptom types because this subscale data were unavailable. For overall symptomatology, topiramate showed a medium, but not significant effect, standardized mean difference (SMD) = 0.55, p = .082. Topiramate showed a small and significant reduction of hyperarousal symptoms, SMD = 0.35, 95% CI [0.029, 0.689], p = .033. Topiramate did not significantly reduce reexperiencing symptoms, SMD = 0.29, 95% CI [−0.019, 0.597], p = .067, or avoidance symptoms, SMD = 0.20, 95% CI [−0.105, 0.509], p = .198. Results did not differ significantly between veteran and nonveteran subjects, or between topiramate as monotherapy and adjunctive therapy. Further studies on topiramate will clarify its role in PTSD treatment.